ICT implementation in elementary school using the Kurikulum Merdeka - Yarania Aristi (Himpunan Pengembang Kurikulum Indonesia, 2026)
The rapid development of digital technology requires elementary schools to integrate Information and Communication Technology (ICT) learning in a relevant manner. Within the framework of the Kurikulum Merdeka, ICT learning plays a strategic role in developing students’ digital skills while fostering character development from an early age. This study aims to explore the implementation of ICT learning as a local content subject at SD Laboratorium Percontohan UPI within the context of the Kurikulum Merdeka. This study employed a qualitative approach using a case study design, involving two ICT teachers who taught both odd-grade levels (Grades 1, 3, and 5) and even-grade levels (Grades 2, 4, and 6), several students, and the school principal. Data were collected through in-depth interviews, participant observation, and documentation analysis. The findings indicate that the implementation of ICT learning at SD Laboratorium Percontohan UPI has been carried out effectively, making a positive contribution to the learning process, with teachers playing a crucial role as active learning facilitators, supported by the use of various digital media. However, several challenges were identified, including limited access to technological devices, unequal internet connectivity across classrooms, and the need for continuous improvement in teachers’ competencies. Abstrak Pesatnya perkembangan teknologi digital menuntut sekolah dasar untuk mengintegrasikan pembelajaran Teknologi Informasi dan Komunikasi (TIK) secara relevan. Dalam rangka Kurikulum Merdeka, pembelajaran TIK memiliki peran strategis dalam mengembangkan keterampilan digital sekaligus membentuk karakter murid sejak dini. Penelitian ini bertujuan untuk mengeksplorasi implementasi pembelajaran TIK sebagai muatan lokal di SD Laboratorium Percontohan UPI dalam konteks Kurikulum Merdeka. Studi ini menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian terdiri dari dua orang guru TIK yang mengajar pada jenjang kelas ganjil (1, 3, dan 5) dan genap (2, 4, dan 6), beberapa murid, serta kepala sekolah. Pengumpulan data dilakukan dengan wawancara mendalam, observasi partisipatif, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa pelaksanaan pembelajaran TIK di SD Laboratorium Percontohan UPI dalam kerangka Kurikulum Merdeka telah berjalan secara efektif dan memberikan kontribusi positif terhadap proses pembelajaran. Peran guru terbukti penting sebagai fasilitator pembelajaran yang aktif, didukung oleh pemanfaatan media digital yang variatif. Kendala yang ditemukan adalah keterbatasan perangkat teknologi, ketidakmerataan akses internet di ruang kelas, dan kebutuhan peningkatan kompetensi guru. Kata Kunci: Kurikulum Merdeka; literasi digital; pembelajaran TIK; sekolah dasar